2008
DOI: 10.1073/pnas.0711757105
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus serotype 5 hexon is critical for virus infection of hepatocytes in vivo

Abstract: Human species C adenovirus serotype 5 (Ad5) is the most common viral vector used in clinical studies worldwide. Ad5 vectors infect liver cells in vivo with high efficiency via a poorly defined mechanism, which involves virus binding to vitamin K-dependent blood coagulation factors. Here, we report that the major Ad5 capsid protein, hexon, binds human coagulation factor X (FX) with an affinity of 229 pM. This affinity is 40-fold stronger than the reported affinity of Ad5 fiber for the cellular receptor coxsacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
374
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(384 citation statements)
references
References 38 publications
9
374
1
Order By: Relevance
“…To achieve liver detargeting, several mutations on capsid proteins, such as the double ablation of CAR and integrin binding, have failed to reduce hepatocyte transduction in vivo owing to the role of blood factors in adenovirus liver transduction. 2,3 Recently, ablation of Factor X binding by the hexon has resulted in successful liver-detargeting, 4,5 although this might be at the expense of lower tumor targeting. 6 Alternatively, the mutation of the heparan sulfate glycosaminoglycan (HSG) putative-binding site KKTK of the Ad5 fiber shaft domain detargets liver transduction, probably because of affectation of the bending or structure of the fiber.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve liver detargeting, several mutations on capsid proteins, such as the double ablation of CAR and integrin binding, have failed to reduce hepatocyte transduction in vivo owing to the role of blood factors in adenovirus liver transduction. 2,3 Recently, ablation of Factor X binding by the hexon has resulted in successful liver-detargeting, 4,5 although this might be at the expense of lower tumor targeting. 6 Alternatively, the mutation of the heparan sulfate glycosaminoglycan (HSG) putative-binding site KKTK of the Ad5 fiber shaft domain detargets liver transduction, probably because of affectation of the bending or structure of the fiber.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Several studies have documented the role of blood coagulation factors in mediating liver gene transfer in vivo and the mechanism underlying Ad5 hepatocyte transduction. [7][8][9][10][11][12] We demonstrated that coagulation factor X (FX) binds to the hexon protein of Ad5 at high affinity (B2 nM) and that this interaction mediates hepatocyte transduction following i.v. delivery in mice and rats.…”
mentioning
confidence: 99%
“…In 2010, Glen Nemerow's group reported the crystal structure of HAdV-5 at 3.5Å resolution, providing new insights into both assembly and structure/function relationships that clearly impact vector design and utility. At the cell:host interaction level, the importance of coagulation factors in adenovirus-mediated gene transfer has unveiled a previously unknown function of the hexon protein in in vivo vector tropism (Kalyuzhniy et al, 2008;Waddington et al, 2008). Subsequent to this, the group of Andrew Byrnes has elegantly shown how this interaction is essential for protection of the virus from immune attack (at least in mice) upon intravenous injection (Xu et al, 2013).…”
Section: Adenovirus-based Vectors: Maximizing Opportunities and Optimmentioning
confidence: 99%